0438 The Impact of Unit Cohesion on Insomnia Symptoms among Army Soldiers. (25th May 2022) - Barilla, Holly; Gehrman, Philip; Brownlow, Janeese; Klingaman, Elizabeth; Miller, Katherine
Abstract: Introduction: Sleep disturbance is common in military personnel and is often related to stressful conditions and deployment to a warzone. Among soldiers, the achievement of unit goals and performance is often dependent upon how cohesive members of the unit are. The quality of unit experiences in terms of reliance on other unit members, feeling respected, and interpersonal relationships could impact the ability to sleep at night. The primary hypothesis of this analysis was that poorer quality unit experiences would be associated with worse sleep at night. Methods: Data were acquired from the All Army Study of the Army Study to Assess Risk and Resilience in Service members (STARRS; N= 21, 449; 28.65 {SD=7.45} years old; 88.24% male). Participants completed the Brief Insomnia Questionnaire, and current insomnia status was determined by DSM-5 criteria. They also completed survey items related to how much respect they had for their officers and other members of their unit as well as how much respect they received in return, their overall morale and if they felt they could rely on members of their unit. T-tests and Chi-square tests were used to examine the associations between insomnia and unit experiences. Results: More negative feelings about unit cohesiveness was associated with higher rates of insomnia (t(19401)= -41.19, p<.0001). Similarly, greater feelings of not being respected by other unit members was associated with higher rates of insomnia (X2 (3, N=19275) = 869.9, p<.0001). Strongly believing that the job reward was not worth the effort that was put into their work also had a significant increase in disturbed sleep (X2 (4, N=19214) = 1120.5, p<.0001). Conclusion: These results demonstrate that, among Army soldiers, poorer quality experiences with other unit members are related to higher rates of insomnia symptoms. Service members who felt they could not rely on other members of their unit, did not feel their officers respected them, and could not speak openly to officers endorsed strong feelings regarding how cohesive their unit was and ultimately reported poorer sleep. Support (If Any): This publication is based on public use data from Army STARRS (Inter-university Consortium for Political and Social Research, University of Michigan-http://doi.org/10.3886/ICPSR35197-v1 ), funded by U.S. NIMH-U01MH087981. KEM's time was supported by the U.S Department of Veterans Affairs, Veterans Health Administration (Clinical Science Research and Development Service – IK2 CX001874). EAK's time was supported by the U.S Department of Veterans Affairs, Rehabilitation Research and Development Service – 1IK2 RX001836.